22.2k views
0 votes
Solve for x.

4 - 3x
---------- = 5
2

User Remario
by
4.7k points

2 Answers

2 votes

Given fractional expression:

{(4-3x)/2} = 5

→ 4-3x = (5)2

→ 4-3x = 10

→ -3x = 10-4

→ -3x = 6

Therefore, x = -(6/3) = -2

User Frank Guo
by
5.0k points
7 votes

Answer:

x=-2

Explanation:

We are given an equation as


(4-3x)/(2) =5

and asked to solve for x

Simplify by multiplying both sides by 2. This will get rid of fraction on left side.

4-3x = 10

Grouping like terms by taking 4 to right side

we get right side 10-4 = 6

-3x = 6

To get exact value of x, we divide by -3 on both the sides

x = 6/-3 = -2





Since this is an equation, we get a single value for x

x=-2

and answer is -2


User Rob Epstein
by
6.0k points